ESPÉCIES DE APIDAE E VESPIDAE ASSOCIADAS À MACRÓFITAS AQUÁTICAS NO PANTANAL DO NABILEQUE - LIMA, Mariza Cunha; PEREIRA, Márlon César; LIMA, Luan Dias; SÚAREZ, Yzel Rondon; ANTONIALLI- JUNIOR, William (ANAIS DO ENIC, 2017)
-